Building Memorable Experiences: The Influence Of Authenticity And Experiencescape On Me Morable Experiences And Re-Visiting Intentions - Atika Putridinanti; Alisa Tri Nawarinir; Asmi Ayuning Hidayah (Journal of Advanced Research in Social Sciences and Humanities, 2025)
Aim: This study aims to determine the effect of authenticity and experiencescape on the intention to revisit natural tourist attractions in Bayumas Regency, namely Curug Jenggala, Curug Telu, Curug Pinang, and Pagubugan Melung with effective experience as mediation. Methodology: The sample in this study was taken using a nonprobability sampling technique with a purposive sampling method. The number of respondents were 120 respondents from the population of visitors to natural tourist attractions in Banyumas Regency. Findings: Using SEM analysis with AMOS software shows the results that authenticity has a positive effect on memorable experiences, experiencescape has a positive effect on memorable experiences, memorable experiences do not have a positive effect on revisit intentions, authenticity has a positive effect on revisit intentions, experiencescape does not have a positive effect on revisit intentions, experience scape does not have a positive effect on revisit intentions, memorable experiences are unable to mediate the influence between authenticity and revisit intentions, and memorable experiences are also unable to mediate the influence between experiencescape and revisit intentions. Implications/Novel Contribution: This study can be implied for managers of natural tourist attractions in increasing revisit intentions. The study provided several unique recommendations and future research directions for scholars and policy makers.